(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
The objective of this paper is to analyse the nature of services provided by collaborative platforms. In this regard, we consider the approach established by the European Commission in its European Agenda on Collaborative Economy, as well as the individual decisions of the Court of Justice which examined the nature of services provided by collaborative platforms Uber and Airbnb. On this basis we formulate the criteria that enable the classification of services provided by collaborative platforms as information society services or as underlying services. As the following step in this analysis we argue that it is necessary to establish not only the nature of services provided by collaborative platforms, but also the nature of the contractual relationships concluded between subjects participating in the collaborative economy.